2022
DOI: 10.31681/jetol.1160476
|View full text |Cite
|
Sign up to set email alerts
|

A Research about the opinions of pre-service Turkish teachers on the online education process

Abstract: The Covid-19 virus, which emerged in Wuhan, China at the end of 2019, spread to the whole world in a very short time and became an pandemic. As a result of the pandemic, some people who had been infected, were put in quarantine process and some people were voluntary in quarantine process, and an online operation was provided in many areas one of which is education. This research, which was designed with the phenomenology method, was conducted to determine the opinions about online education process of 72 stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…A study of pre-service English teachers in Hong Kong found that online education provided limited opportunities for immediate and extensive feedback (Atmaca, 2023). Yildirim (2022) explored 72 pre-service teachers' perceptions of online education during the pandemic, finding that 80% considered face-to-face classes more productive. Participants identified contributory factors including internet connection problems, digital literacy, readiness for online learning, lack of communication and interaction, lack of motivation and selfregulation, and feedback mechanisms.…”
Section: Quality Of Online Teachingmentioning
confidence: 99%
“…A study of pre-service English teachers in Hong Kong found that online education provided limited opportunities for immediate and extensive feedback (Atmaca, 2023). Yildirim (2022) explored 72 pre-service teachers' perceptions of online education during the pandemic, finding that 80% considered face-to-face classes more productive. Participants identified contributory factors including internet connection problems, digital literacy, readiness for online learning, lack of communication and interaction, lack of motivation and selfregulation, and feedback mechanisms.…”
Section: Quality Of Online Teachingmentioning
confidence: 99%